Gastric pneumatosis: An unusual presentation of superior mesenteric artery syndrome - Natalie A. Drucker; Megan B. Marine; Frederick J. Rescorla (Elsevier, 2018)
We present a case of extensive gastric pneumatosis with portal venous air due to superior mesenteric artery syndrome in an underweight, developmentally normal seventeen-year-old boy. Despite his alarming imaging findings, his abdominal exam was benign and he was successfully treated nonoperatively. Keywords: Gastric pneumatosis, Superior mesenteric artery syndrome, Wilkie's syndrome